Prevalence of congenital heart diseases among primary school children in the Niger Delta Region of Nigeria, West Africa - Susan, Ujuanbi Amenawon; Nnena, Tabansi Petronilla; Edewele, Otaigbe Barbara (Journal of Cardiology and Cardiovascular Medicine, 2019)
Introduction: Congenital heart diseases (CHD) are leading causes of childhood morbidity and mortality especially in developing countries. Community-based studies are important in ascertaining the burden of the disease. Objectives: The study was set out to determine the prevalence and types of CHD among primary school children in Port Harcourt Local Government Area (PHALGA) of Rivers State, Niger Delta, Nigeria. Methods: A total of 1,712 primary school pupils were selected by multistage sampling from twelve schools in PHALGA. A questionnaire was used to obtain information from pupil’s parents on their child’s biodata and symptoms suggestive of heart disease. General physical and cardiovascular system examinations were carried out on each selected pupil, following which those with symptoms and/or signs suggestive of heart disease had echocardiographic confirmation of their cardiac status. Results: The 1,712 subjects were aged 5-14 (mean 8.48 ± 2.30) years. 874 (51.1%) were females while males were 838 (48.9%). The study revealed that 31 pupils had congenital heart diseases confirmed by echocardiography, giving a prevalence of 18.1 per 1,000 pupils. The commonest cardiac defects seen were acyanotic CHD in 30 (96.8%) pupils while cyanotic CHD was seen in only one (3.2%) pupil. Among the acyanotic CHD, atrial septal defects (83.9%) followed by ventricular septal defects (9.7%) were the commonest. CHD occurred with higher frequency among females (64.5%) and among the younger age group of 5-9 years (61.3%) though these were not statistically significant (p > 0.005). Conclusion: Cardiac examination as part of compulsory health screening at primary school entry will help detect children with CHD, reduce delay in diagnosis for intervention, avert debilitating morbidity and assure a better quality of life.